Characteristics of spray drying process of nanocolloidal silica as a method of production of nanostructural powders potentially applicable in inhalation therapy - Jabłczyńska, Katarzyna; Wojnarowicz, Michał; Sosnowski, Tomasz R. (Lviv Polytechnic Publishing House, 2015)
The research was focused on investigations of the impact of spray-drying (SD) conditions on the morphology and aerosol performance of powders produced from nanocolloidal silica. Microsized nanostructiral particles were characterized by SEM, aerosol spectrometry and pharmaceutical impactor. Results show that proper adjusting of SD process parameters and precursor composition allows to obtain powders of different morphologies: solid or hollow particles with different wall thickness, or particles with a microporous structure with spherical or nonspherical shape. Obtained results indicate that silica nanoagreggates have characteristics suitable for their effective delivery to the lungs via inhalation.
Keywords: spray drying; nanostructural powder; particles engineering; silica particles; inhalation therapy